Motivations Associated with Food Choices among Adults from Urban Setting - Ilić, Ana (2023)
Motivation for food choices is one of the most important determinant of eating behavior, because it comes from within the person. The aim of this study was to observe food choice motivations and estimate differences in demographic and health characteristics towards food choice motives in the adult population (n = 675; 54% women, ≥18 years) from urban setting. Food choice motivations were assessed using an online questionnaire validated by the EATMOT project. Using K-Means cluster analysis, participants were divided into two clusters of six motivational categories for food choices. Regarding the most and least important motivations, participants in cluster 1 chose food based on emotional motivations, and in cluster 2, they chose based on environmental and political motivations. In addition, younger and obese individuals had more pronounced emotional motivations. In conclusion, this study emphasizes the need to address emotional motivations for healthier food choices among overweight and young people. In addition, the prevalence of health motivations and growing awareness of sustainability indicate a willingness to take actions that benefit personal health and the environment. Apart from providing education, it is society’s responsibility to create an environment that promotes the implementation of acquired knowledge and changes in dietary habits.